Pengaruh Experiential Marketing Dan Sales Promotion Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Pelanggan Go-Ride Semarang - Wiranti M.S Hutabarat; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2020)
Ride hailing is a transportation that utilizes an online platform by connecting passengers and drivers. In Indonesia hailing is growing rapidly marked by the presence of similar services. PT Gojek Indonesia is a pioneer hailing ride with Go-Ride services. The Gojek application was launched in January 2015 with the Go-Ride feature. Now Gojek has grown to 14 services with millions of downloads accompanied by 2 million driver partners spread across 203 cities. This study aims to determine the effect of experiential marketing and sales promotion on customer loyalty through Go-Ride customer satisfaction.  This is explanatory research, sampling using nonprobability sampling techniques, purposive sampling method. Data collection using the google form online questionnaire. The sample used was 100 Go-Ride Semarang respondents. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficient, determination coefficient, simple and multiple regression, t test, F test, and sobel test. The Sobel test results state that customer satisfaction is able to partially mediate between experiential marketing and sales promotion on customer loyalty. The correlation coefficient of experiential marketing and sales promotion variables to customer satisfaction has a strong relationship. The coefficient of determination of customer loyalty can be explained as much as 53.4%  by customer satisfaction. The coefficient of determination of customer satisfaction can be explained worth 60.7% by experiential marketing and sales promotion.